THE CATEGORY OF AFFIRMATION AND NEGATION IN POETIC SPEECH - Matyakupov, Sa’dulla Gaypovich (SCIENCE and SOCIETY, 2026)
This article explores the forms of dialogue in poetic speech and the relationship between the categories of affirmation and negation within them. The article examines the manifestations of this phenomenon, its theoretical foundations, and its influence on poetic structure. The results of a scientific and theoretical analysis of this phenomenon's reflection in world and Uzbek poetry are summarized.
Keywords: poetic speech; dialogue; monologue; worldview; artistic communication